Anatomic distribution of supraclavicular lymph node in patients with esophageal cancer - Xing, Jun (Onco Targets Ther, 2016)
PURPOSE: Definitive chemoradiation therapy remains the standard of care for patients with localized esophageal carcinoma who choose nonsurgical management. However, there is no consensus regarding delineation of the nodal clinical target volume (CTVn), especially for lower cervical lymph nodes. This study aimed to map the location of metastatic supraclavicular lymph nodes in thoracic esophageal carcinoma patients with supraclavicular node involvement and generate an atlas to delineate the CTVn for elective nodal radiation of esophageal squamous cell carcinoma. PATIENTS AND METHODS: In this study, the supraclavicular regional lymph node was further divided into four subgroups. The locations of the involved supraclavicular nodes for all patients were then transferred onto a template computed tomography (CT) image. A volume probability map was then generated with nodal volumes, and was displayed on the template CT to provide a visual impression of nodal frequencies and anatomic distribution. RESULTS: We identified 154 supraclavicular nodal metastases based on CT image in 96 patients. Of these, 29.2% were located in group I region, 59.7% in group II region, 10.4% in group III region, and 0.7% in group IV region. CONCLUSION: On the basis of our study, we suggest that the appropriate radiation field of CTVn should include the group I and II regions and the CTVn exterior margin along the lateral side of the internal jugular vein may be suitable.